VIDEO BLOGGING AS AN INNOVATIVE FORM OF THE PROJECT ACTIVITY IN FOREIGN LANGUAGE TEACHING TO JOURNALISM STUDENTS - M. V. Petrova (Russian State Vocational Pedagogical University, 2018)
Introduction. The appearance of new formats and ways of presenting information inevitably affects the educational process and leads to the necessity to revise the paradigm of pedagogical attitudes and tools of the teaching activity, which in turn generates a number of methodological and didactic problems to be solved. The relevance of the research topic is caused by the current tendency of the distribution of video blogging as an information activity tool that affects the educational environment. There is a steady development of video blogging (a special kind of blog, where the emphasis is made on video information) as a new channel of communication in the educational services market, and using it as a separate form of non-educational project activity within the framework of mastering one or another academic discipline. In the conditions of deficiency of classroom hours and increase in student independent work, project-based education is becoming more and more demanded type of training. Currently, interdisciplinary projects are being widely disseminated at high school; these projects are aimed at vocational guidance for a foreign language, they meet the requirements of the new communication reality and the needs of modern educational systems. The aim of the publication is to consider video blogging as an innovative form of project-oriented learning a foreign language and to characterize the features of creating and implementing media content within the framework of a foreign language training course. Methodology and research methods. In the course the research, such theoretical scientific methods as analysis, synthesis, concretization, generalization, as well as hypothetical-deductive and design methods were applied. Results and scientific novelty. For the first time the article deals with the structure of video blogging as a project work and as a form of professionally oriented foreign language teaching as well, also there are formulated basic didactic questions in the article. These questions have appeared in the process of the development and the implementation of the media project "Episch! Deutsch", created in 2015 within the framework of the subject "German language" at the Department of Media Linguistics of the Faculty of Journalism of Moscow State University named after M. V. Lomonosov. The conclusion is made that it is necessary to develop methodological criteria and educational standards that regulate video blogging as a way of teaching and methodological work, also a providing an opportunity for development of teachers' professional qualification. Practical significance. The materials of the present publication can be useful for future and practicing teachers of a foreign language, as well as for other categories of educators engaged in organization of educational project activities.